Paradoxical phenomena of bullous pemphigoid induced and treated by identical biologics - Zhang, Jie; Wang, Si-Hang; Zuo, Ya-Gang (Frontiers in Immunology, 2023)
Objective: The aim of this study was to investigate the clinical features of biologics-induced bullous pemphigoid (BP) as well as the therapeutic effect of those agents for BP and explore the underlying pathophysiological mechanisms. Methods: We searched PubMed, Web of Science, and Elsevier for studies involving pemphigoid patients treated with or induced by biologics for psoriasis published in English from January 2009 to April 2022. Results: Seventeen cases of drug-induced BP associated with anti-TNF-α therapies, one with IL-17 inhibitors and seven with IL12/IL23 inhibitors were enrolled. Time to cutaneous toxicity varied among different types of agents and the characteristics of laboratory examinations were similar to those of idiopathic BP. Discontinuation of the culprit drugs and initiation of topical or systemic corticosteroids were effective in most cases. Several monoclonal antibodies have been reported for the treatment of refractory or cortico-dependent BP especially concurrent with psoriasis. Conclusion: Biologics for psoriasis including TNF-α, IL-17 and IL12/IL23 inhibitors can both induce and treat BP, which might be associated with Th1/Th2 imbalance, the complicated inflammatory networks and specific individual micro-environment, providing a new perspective on the therapeutic algorithm of BP.